Islamic Economic Approach to Strengthening Public Purchasing Power through Price Stabilisation Policy - Hawanda, Maisyah; Atika, Atika; Tambunan, Khairina (Universitas Trunojoyo Madura, 2024)
This study aims to evaluate the efficiency of stable price policies in enhancing the purchasing power of households in the framework of Islamic Economy.This study applies a qualitative research methodology, using case study approaches to analyze the data through a descriptive approach. A case study was initiated to investigate the stability of rice prices in the city of Medan as a result of government intervention. A data collection method that involves conducting an analysis in a library. Secondary data sources encompass scientific journals, books, official government publications, and pertinent statistical data.The study's findings demonstrate that the government's enforcement of price stability policy effectively enhances the purchasing power of households. The Islamic Economy Review emphasizes that the policy of stabilizing rice prices must consider the principles of justice and public welfare. After conducting research and reviewing the Islamic economy, it has been determined that there are several steps in which should be implemented to enhance the effectiveness of the rice price stabilization policy. These steps include enhancing market operating programs and providing direct cash financial assistance, building the development of the local economy, empowering grain farmers, improving education and public participation, implementing the principles of Islamic economy in the price stabilization policy, and strengthening surveillance and law enforcement.The study helped improve the performance of price stability programs, possibly strengthening public purchasing power and strengthening equitable economic and social conditions in line with the principles of Islamic Economy.